The effects of the liberalisation of capital controls with respect to the inflow of foreign direct investment in the mining industry in South Africa - Maitho, Edwin (Research of GSB, 2018)
South Africa has in the recent past endeavoured to attract foreign direct investment through the liberalisation of capital controls. The question that has been raised is whether, in the wake of the recent global financial crisis and the corresponding response of economists that now more than ever the re-introduction of capital controls is necessary, the liberalisation of capital controls in South Africa is necessary. Therefore the study endeavours to investigate, taking cognisance of the pecularity of the country, whether the liberalisation of capital controls in the form of exchange controls has had a positive effect in attracting foreign direct investment. Other determinants of foreign direct investment are considered to identify whether focus should perhaps be on these determinants to inform policies implemented to attract foreign direct investment.